2014
DOI: 10.1371/journal.pone.0100798
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV Inhibitor MK-0626 Attenuates Pancreatic Islet Injury in Tacrolimus-Induced Diabetic Rats

Abstract: BackgroundTacrolimus (TAC)-induced pancreatic islet injury is one of the important causes of new-onset diabetes in transplant recipients. This study was performed to evaluate whether a dipeptidyl peptidase IV (DPP IV) inhibitor is effective in improving TAC-induced diabetes mellitus by reducing pancreatic islet injury.MethodsRats were treated with TAC (1.5 mg/kg, subcutaneously) and the DPP IV inhibitor MK-0626 (10 or 20 mg/kg, oral gavage) for 4 weeks. The effect of MK-0626 on TAC-induced diabetes was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…The whole-blood SRL concentration was measured using a microparticle enzyme immunoassay (Abbott Diagnostics, Abbott Park, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT In vitro study. As shown in our previous study, the protective effects of DPP IV inhibitors are associated with activation of glucagon-like peptide 1 (GLP-1) (18). To investigate the exact role of the combined treatment with a DPP IV inhibitor and MET on SRL-induced pancreatic beta cell injury, we applied the GLP-1 analog exendin-4 (EXD) (0.01nM; SigmaAldrich, St Louis, MO) and MET (10ng/mL) to INS-1 cells, which was donated by Dr. Yoon 50 µM β-mercaptoethanol, 100 U/mL penicillin, and 100 mg/mL streptomycin (except for FBS, all were from Sigma-Aldrich).…”
Section: A N U S C R I P Tmentioning
confidence: 74%
See 1 more Smart Citation
“…The whole-blood SRL concentration was measured using a microparticle enzyme immunoassay (Abbott Diagnostics, Abbott Park, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT In vitro study. As shown in our previous study, the protective effects of DPP IV inhibitors are associated with activation of glucagon-like peptide 1 (GLP-1) (18). To investigate the exact role of the combined treatment with a DPP IV inhibitor and MET on SRL-induced pancreatic beta cell injury, we applied the GLP-1 analog exendin-4 (EXD) (0.01nM; SigmaAldrich, St Louis, MO) and MET (10ng/mL) to INS-1 cells, which was donated by Dr. Yoon 50 µM β-mercaptoethanol, 100 U/mL penicillin, and 100 mg/mL streptomycin (except for FBS, all were from Sigma-Aldrich).…”
Section: A N U S C R I P Tmentioning
confidence: 74%
“…Therefore, the ideal antidiabetic drugs to treat SRLinduced DM should work by improving impaired insulin signaling and protecting against islet cell injury. We tested the combination of MET and a DPP IV inhibitor after considering previous reports showing that MET improves the insulin signaling pathway by activating AMP-activated protein kinase (44) and that DPP IV inhibitors can protect against pancreatic islet cell injury caused by diverse injuries (9), including tacrolimus-induced renal and pancreatic islet injuries (18,19). Thus, we hypothesized that the combination of MET and a DPP IV inhibitor would provide better control of SRL-induced DM compared with each drug alone.…”
Section: Cellsmentioning
confidence: 99%
“…Exendin-4, another GLP-1R agonist, protects endothelial cells from palmitate-induced apoptosis by modulating stress-sensitive signaling pathways ( 40 ). In a previous study, in rats with tacrolimus-induced diabetes, the dipeptidyl peptidase-4 (DPP4) inhibitor, MK-0626, decreased the levels of 8-OHdG (a marker of oxidative DNA damage) and increased the levels of manganese superoxide dismutase and heme oxygenase-1 ( 41 ). In rats with streptozotocin-induced diabetes, liraglutide was shown to directly protect the rats against oxidative stress through the inhibition of NAD(P)H oxidases ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has an important role in the pathogenesis of Tac-induced pancreatic islet injury. 4,13 Therefore, we evaluated the effect of KRGE on mitochondria, which are susceptible to oxidative damage and are one of the major cellular sources of ROS generation. 14,15 In this study, Tac decreased overall mitochondrial function, demonstrated by increased mitochondrial ROS, superoxide anion production, mitochondrial membrane depolarization, and reduced mitochondrial bioenergetics.…”
Section: Discussionmentioning
confidence: 99%